2011
DOI: 10.1186/1758-5996-3-24
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of fenofibrate on C-reactive protein: A meta-analysis of randomized controlled trials

Abstract: BackgroundC-reactive protein (CRP) is positively associated with risk for cardiovascular disease and all-cause mortality. Some but not all randomized and non-randomized clinical trials found significant associations between fenofibrate therapy and CRP but the direction and magnitude of the association varied across studies. The duration of treatment, patient populations and sample sizes varied greatly, and most short-term studies (i.e., ≤ 12 weeks) had fewer than 50 patients. In this study we meta-analyzed ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…Findings from the sensitivity analysis implied that the detected significance for the efficacy of L-carnitine is robust and not considerably affected by a single study. It is interesting to note that the weighted pooled estimate for the effect of L-carnitine on circulating levels of CRP is greater than those reported from previous meta-analyses on soy isoflavones ( 40 ) and telmisartan ( 41 ), but lower than those of fibrates ( 42 ) and statins ( 6 ).…”
Section: Discussionmentioning
confidence: 62%
“…Findings from the sensitivity analysis implied that the detected significance for the efficacy of L-carnitine is robust and not considerably affected by a single study. It is interesting to note that the weighted pooled estimate for the effect of L-carnitine on circulating levels of CRP is greater than those reported from previous meta-analyses on soy isoflavones ( 40 ) and telmisartan ( 41 ), but lower than those of fibrates ( 42 ) and statins ( 6 ).…”
Section: Discussionmentioning
confidence: 62%
“…Also, other studies showed antithrombotic and fibrinolytic properties of fenofibrate (decrease in PAI and fibrinogen), 54 neo-angiogenesis reduction, and, on the other side, increase of flow-mediated dilation consistent with beneficial improvement of nitric oxide production, as proved in vitro. 44 …”
Section: Fenofibratementioning
confidence: 61%
“…Last, markers of inflammation as CRP, interleukins (mostly interleukin-6 [IL-6] and tumor necrosis factor-α [TNF-α]), adhesion molecules (VCAM and ICAM) and uric acid were reduced with the administration of fenofibrate in a high-risk group. 52 54 …”
Section: Fenofibratementioning
confidence: 99%
“…Impact of Drugs on hsCRP. 3,[23][24][25][26][27][28][29][30]43 Drug or Class Magnitude of hsCRP Reduction Aspirin, 23 ACE inhibitors, [24][25][26] fibrates 28~2 0%-30% Statins 29~3 0%-50% Canakinumab 3,43~4 0%-60% [~25%-40% when combined with ACE inhibitors and statins] Methotrexate 30~7 0%…”
Section: Traditional Drugs To Suppress Inflammation and Reduce Ascvd mentioning
confidence: 99%